Teaching Strategies and Space Organisation in Multigrade Classrooms - Pilar Abós-Olivares; Antonio Bustos-Jiménez (Universidade de Lisboa, 2015)
This paper presents the outcomes of one of the phases of an international research project which studied several dimensions of teaching in rural schools -Project EDU2009-13460, Sub-programme EDUC (Spanish Ministry of Science and Innovation); participant countries: Spain, France, Portugal, Chile and Uruguay. The outcomes of two dimensions researched in the Spanish territory, namely teaching strategies and space organisation, are presented. For that, attention was focused in education centres and classrooms where, according to the results of a previous research, there seemed to be present active and participatory methods. Qualitative research method was used in this phase of the research; teachers from multigrade classrooms were interviewed so as to obtain the information presented in this paper. The outcomes achieved offer information related to the understanding and application of the methodology on the part of the interviewed teachers. Several pedagogic options within the framework of differences in age and grade, as well as the possibilities they took into account about space organisation in the classroom and in the education centres, are presented.